FORMATION OF THE TERRITORIAL DEVELOPMENT OF UKRAINE AND CHINA - and (Municipal economy of cities. Series: «Economy science», 2018)
The article is devoted to solving an important scientific and practical task of ensuring the territorial development of Ukraine and China. The purpose of the article is to determine the directions and features of the territorial development of Ukraine and China. To achieve this goal in the work set the following tasks: to study the theoretical approaches to the definition of territorial development; to identify features of the territorial structure of Ukraine and China; to analyze directions of territorial development of Ukraine and China; determine the ways of increasing the efficiency of functioning of the united territorial communities. In order to ensure territorial development in Ukraine on the basis of the establishment of united territorial communities, taking into account international experience and identified trends in the autonomy of entities in China, the proposed ways: examination of land and property complex, land valuation, increase of its completeness and quality; creation of the system of geospatial data on the land-property complex of the united territorial communities; to develop zone zoning; formation and implementation of land, town-planning, geo-ecological monitoring of the use of land-property complex of united territorial communities. Keywords: territorial development, territorial structure of Ukraine and China, united territorial communities.